اثر اﺴﺘراﺘﯿﺠﯿﺎت ﺘﻨﻤﯿﺔ اﻟﻤوارد اﻟﻤﺎﻟﯿﺔ ﻓﻲ ﺴﯿﺎﺴﺎت اﻻﺌﺘﻤﺎن اﻟﻤﺼرﻓﻲ: دراﺴﺔ ﺘﺤﻠﯿﻠﯿﺔ ﻓﻲ ﻤﺼرف اﻟرﺸﯿد (Journal of Accounting and Financial Studies ( JAFS ), 2006)
The recent strategic thought requires research and study to indicate the bankssuitable which enable them to protect its location in the market and to face thechallenges that appeared in the 20 – first century.The research aims at shedding light upon the effect of financial resources growthstrategic to a bank loan policy.A questionnaire of ( 30 ) managers, with in different management levels , wasused.In order to test hypotheses, the present research has relied upon ( MultipleRegression ) to the influence being exerted at a level ranging between(0.01,0.05,0.10) The analysis of hypotheses also started a number ofrecommendation that might contribute in rising the standard of applying bankingIraqi sector to protect the organization competitive location in the market.